Optimasi Sudut Ujung Pipa Penangkapan Gas Metana Pada Metode Arrow System - Septiropa, Zamzami; Fauzan H.S, Achmad; Zainuddin, Moch. (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
Drilling system on a pile of waste to get the methane gas is very difficult because the majority of waste that is made from plastic so it can get caught in the drill. Manual excavationis not allowed because it is very dangerous, while digging with heavy equipment has not been able to do because it requires a special tool that is able to push and pull waste surface. Makingholes with arrow system method that is larger arrowhead from the arrow shaft, is one alternative that can be tried to get a hole / gas extraction wells at the Landfill Supit Urang - Malang.Results hole larger than the arrow shaft is then filled with gravels as well extration methane in the landfill. The force required pile (arrow system) to the pole with pole diameter 26.7 cm and a maximum depth of 5.20 m (at point 1, the arrows point of 30Ëš and 45Ëš) is a row of 63,087 kg and 79,717 kg . Optimum angle in terms of penetration force needs is the pole with arrowhead angle 30Ëš.